Circulating Anti-Beta2-Glycoprotein I Antibodies Are Associated with Endothelial Dysfunction, Inflammation, and High Nitrite Plasma Levels in Patients with Intermittent Claudication - Cesar Varela; Joaquin de Haro; Silvia Bleda; Leticia Esparza; Ignacio Lopez de Maturana; Francisco Acin (Hindawi Limited, 2013)
Our aim is to investigate a possible association of circulating anti-beta2-glycoprotein I antibodies (ABGPI) with the endothelial dysfunction, nitric oxide bioactivity dysregulation, and the inflammatory status that surrounds peripheral arterial disease. We carried out an observational translational study, including 50 male patients with intermittent claudication and a healthy control group of 10 male subjects, age and sex matched with the cases. Flow-mediated arterial dilatation (FMAD) was assessed as a surrogate of endothelial dysfunction, and C-reactive protein (hsCRP) was determined as a marker of inflammation. Nitrite plasma levels were measured by colorimetric analysis. Circulating ABGPI titer was detected with indirect immunofluorescence. Titers <1 : 10 represented the reference range and the lower detection limit of the test. Circulating ABGPI titer ≥1 : 10 was detected in 21 (42%) patients and in none of the control subjects (P<0.01). Patients with ABGPI titer ≥1 : 10 had a lower FMAD (P=0.01). The CRP levels were higher in patients with ABGPI titer ≥1 : 10 (P=0.04). The nitrite plasma levels were higher in patients with ABGPI titer ≥1 : 10 (P<0.01). These data suggest that these circulating ABGPI may collaborate in the development of atherosclerosis; however, further prospective studies are required to establish a causal relationship.